Peran Pemanfaatan Digital Marketing dalam Peningkatan Kinerja dan Keberlanjutan UMKM - Noviana Puspitasari; Dody Mulyanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study analyzes the role of digital marketing in improving the performance and sustainability of water tourism MSMEs in Klaten Regency. A quantitative approach was used, surveying 155 MSME actors selected via purposive sampling. Data were analyzed with SmartPLS to examine variable relationships and Sobel tests for mediation analysis. Results reveal that digital marketing significantly influences MSME performance and sustainability. Beyond direct effects, digital marketing also indirectly contributes through MSME performance as a mediator. This supports the resource-based view and triple bottom line theories, highlighting the importance of technological innovation for efficiency and competitiveness. However, technology adoption remains limited in areas with restricted digital infrastructure access. MSMEs are advised to enhance digital literacy and adopt strategies like social media and SEO. The government should provide continuous training and expand digital infrastructure to support MSME transformation. Future research should broaden geographic and sectoral scopes and explore advanced technologies like artificial intelligence to enhance MSME performance and sustainability.